Resource reviews - Petro Naude (Environmental Association of Southern Africa, 1987)
1. Petro Naude Walk through the wilderness by Don Richards and Clive. Walker. Published by Endangered Wildlife Trust and Wilderness Trust of Southern Africa, Johannesburg. Second (revised) edition 1986. 146 pp., photographs, maps, charts and line drawings. Price R9,95. 2. Pat Irwin Trout in South Africa edited by P.H. Skelton & M. T. T. Davies: Ichthos Newsletter Special Edition No. 1. Publ Institute of Ichthyology, Grahamstown 1987. 20 pp. Price R3,00. 3. Anne Curror Teaching children through the environment by Pamela Mays. Published by Hodder & Stoughton, London 1985. 4. Francis Gamble The urban environment by I. Douglas. Published by Edward Arnold, London 1983. 229 pp. tables, maps, diagrams, photographs, references, index. 5. Julie Wilcocks National parks: Wildlife game and colouring book Enviro-Vision Series published by Shuter & Shooter, 1986. R2,65. Available in English and Afrikaans 6. Pat Irwin The making of the museum professions in Southern Africa by C.K. Brain & M.G. Erasmus. Published by the Transvaal Museum in association with the Southern African Museums Association, Pretoria 1986. 46 pp. Price R5,00.